Microbiome analysis of andean soils and high-throughput molecular aproaches for translational epidemiology of early blight - Alvarez Romero, Pablo Israel (2019)
Early blight (EB) is one of the most devastating foliar diseases of solanaceous crops. As chemical control is the main strategy used to control EB, the active microbiota of the soil has the potential to help to managing plant diseases. It was demonstrated that the microbiota associated with Andean soils has an important role in potato diseases suppressiveness. Based in this hypothesis we used high-throughput sequencing (HTS) and metabarcoding to investigate the composition, structure, and diversity of microbiota associated with the rhizosphere of native (landraces) and improved potatoes (commercial) from the Ecuadorian Andes as a quest for potential biological control agents of early blight. The main fungi phyla found were Ascomycota (51.96%), Mortierellomycota (28.39%) and the Basidiomycota (5.56%), while bacterial community was dominated by the Proteobacteria (39.17%), Acidobacteria (17.89%), and Bacteroidetes (14.10%) phyla. Edaphic factors affected the composition, diversity, and structure of the microbiota across the different places sampled. Higher microbial diversity was found in the rhizosphere from landrace cultivars and it constitutes a new source of candidate microorganisms for the use in biological control. Moreover, we used an ecological approach involving reciprocal soil transplant to test the effect of putative suppressive Andean soils to potato and tomato EB epidemics. The direct transfer of soil had an effect only on the epidemics on potato EB. The rhizosphere microbiome from the plants was structured by soil and crop type. Highest levels of fungal diversity were found in potato rhizosphere associated with Ecuadorian soils. Also in the same study, we used HTS and metabarcoding to assess the temporal variation of the fungal and bacterial leaf-microbiota associated with potatoes and tomatoes plants growth in Brazilian and Ecuadorian soils and infected by different species of Alternaria. The leaf profile of microbiota composition was affected by the soil transfer. Thirteen families of fungi belonging to the Ascomycota phylum and 15 families belonging to the Basidiomycota were found in potatoes associated with Brazilian soils, in contrast, eight families of fungi belonging to Ascomycota phylum and 17 families belonging to the Basidiomycota phylum were found in potatoes associated with Ecuadorian soils. Also, 15 families of Fungi belonging to Ascomycota and 10 families belonging to Basidiomycota were found in tomatoes grown in Brazilian soil while, respectively, 14 and 16 families were recorded in plants grown in Ecuadorian soil. Finally, to differentiate closely related species of Alternaria associated with EB in potato and tomato crops, a single round polymerase chain reaction coupled with high-resolution melting curve (PCR-HRM) using primers for the cadmodulin gene were develop and validated. The HRM-assay was a useful diagnostic tool. All techniques explored in this thesis may enhance management strategies for early blight epidemics. Keywords: Metabarcoding. Sequencing. Soil Suppressiveness. Alternaria. PCR. Population biology.